Immunology in Africa. Issue 12 (12th October 2015) - Cose, Stephen; Bagaya, Bernard; Nerima, Barbara; Joloba, Moses; Kambugu, Andrew; Tweyongyere, Robert; Dunne, David W.; Mbidde, Edward; Kaleebu, Pontiano; Elliott, Alison M.
Abstract: Africa is a continent with a large burden of both infectious and non‐communicable diseases. If we are to move forward as a continent, we need to equip our growing cadre of exceptional young scientists with the skills needed to tackle the diseases endemic to this continent. For this, immunology is among the key disciplines. Africans should be empowered to study and understand the diseases that affect them, and to perform their cutting‐edge research in their country of origin. This requires a multifaceted approach, with buy‐in from funders, overseas partners and perhaps, most important of all, African governments themselves.